The potential role of transient receptor potential type A1 as a mechanoreceptor in human periodontal ligament cells. (31st August 2013) - Tsutsumi, Takashi; Kajiya, Hiroshi; Fukawa, Teruhisa; Sasaki, Mina; Nemoto, Tetsuomi; Tsuzuki, Takashi; Takahashi, Yutaka; Fujii, Shinsuke; Maeda, Hidefumi; Okabe, Koji
Abstract : Transient receptor potential type A1 (TRPA1) is reported to be a Ca 2+ ‐permeable channel and is activated by cold temperatures and mechanical stimuli in the hair cells and in dorsal root ganglion. Using a DNA microarray, we found that TRPA1 was significantly up‐regulated in human periodontal ligament (hPDL) cells 2 d after intermittent mechanical stimulation (iMS) loading compared with unloaded cells. Although hPDL cells are known to respond to mechanical stimulation induced by occlusal force, little is known about the expression and functional role of TRPA1 in these cells. Therefore, we investigated the effects of iMS on TRPA1 expression and its signaling pathway in hPDL cells. Intermittent mechanical stimulation loading up‐regulated TRPA1 expression in hPDL cells in a time‐dependent manner, but had no effect on other mechanoreceptors. Furthermore, iMS significantly increased the phosphorylation of mitogen‐activated protein kinases (MAPKs), especially extracellular signal‐regulated kinase 1/2 (ERK1/2) and p38, and the expression of C‐C chemokine ligand 2 (CCL2). Transient receptor potential type A1 agonists also increased MAPK phosphorylation and the intracellular Ca 2+ concentration. By contrast, inhibition or silencing of TRPA1 partially suppressed iMS‐induced MAPK phosphorylation. In summary, iMS during occlusion activates TRPA1 and MAPK signaling in periodontal ligament tissues, suggesting that TRPA1 regulates the mechanosensitivity of occlusal force via activation of MAPKs in hPDL cells.